2010
DOI: 10.1161/strokeaha.110.585067
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Thrombolysis for Chronologically Separated Ischemic Strokes

Abstract: Background and Purpose-Recombinant tissue plasminogen activator is used for the treatment of acute myocardial infarction, pulmonary embolism, and acute ischemic stroke. With many years since approval of the drug and an aging population, chances increase that patients are treated twice for chronologically separated events. Methods-We identified patients from the prospective Erlangen Stroke and Thrombolysis Database who received repeated thrombolysis for acute ischemic stroke. Baseline demographic data and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Although repeated systemic thrombolysis has been reported to be safe and efficient for patients presenting with a recurrent AIS [3,4,5,6], its use carries the limitations inherent to tissue plasminogen activator (t-PA) including bleeding risk mostly if the recurrence is relatively early on [15]. Intravenous t-PA re-administration has also been associated with severe immune reactions [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although repeated systemic thrombolysis has been reported to be safe and efficient for patients presenting with a recurrent AIS [3,4,5,6], its use carries the limitations inherent to tissue plasminogen activator (t-PA) including bleeding risk mostly if the recurrence is relatively early on [15]. Intravenous t-PA re-administration has also been associated with severe immune reactions [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Although repeated thrombolytic therapy has been reported safe and beneficial for recurrent strokes [3,4,5,6], the data regarding repeat thrombectomy (RT) is scarce and limited to a few case reports [7,8,9]; therefore, its safety and potential efficacy remain elusive. We aim to report our local experience with RT for recurrent LVOS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although patients with a prior stroke have been historically considered to be at high risk of ICH after t-PA therapy, multicenter registries, including the Safe Implementation of Thrombolysis in Stroke-Monitoring Study registry, showed that prior stroke was not related to sICH [24,25]. A recent case series reported a patient who was successfully treated using t-PA therapy after he had sICH due to prior stroke [26]. These findings support the present study finding that patients with hemorrhagic transformation due to prior stroke may not be at higher risk of developing ICH after t-PA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The large multicenter studies that led to the approval and the extension of the time window of rt-PA in ischemic stroke explicitly excluded patients who had received rt-PA within 3 months of the actual event [10,18] . Thus, data concerning this important clinical question are limited to case reports and series of very small patient numbers [19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%